2019
DOI: 10.1002/tal.1659
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flexural natural vibrations of thin‐walled box beams using higher order beam theory

Abstract: Summary In order to study the influence of high‐order shear deformations and shear lag on the dynamic characteristics of thin‐walled box beams (TWBBs), this paper takes the Hamilton principle as a basis to consider multiple factors such as high‐order shear deformations, shear lag, and cross section rotary inertia of the TWBBs. The vibration differential equations and natural boundary conditions of TWBBs are deduced. On the basis of eight examples of TWBBs with different boundary conditions and span–width ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Zhou et al [34] theoretically investigated the dynamic characteristics of steel-concrete composite box beams considering the SLE and slip by introducing self-balancing of axial forces in a longitudinal warping function of beam section. Jiang et al [35] studied the influence of high-order shear deformations and SLE on the dynamic characteristics of thin-walled box beams by using highorder beam theory. They concluded that the SLE increase with the increasing of mode order or the decreasing of span-width ratio.…”
Section: Studies On the Shear Lag Effect (Sle) And Research Gapsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhou et al [34] theoretically investigated the dynamic characteristics of steel-concrete composite box beams considering the SLE and slip by introducing self-balancing of axial forces in a longitudinal warping function of beam section. Jiang et al [35] studied the influence of high-order shear deformations and SLE on the dynamic characteristics of thin-walled box beams by using highorder beam theory. They concluded that the SLE increase with the increasing of mode order or the decreasing of span-width ratio.…”
Section: Studies On the Shear Lag Effect (Sle) And Research Gapsmentioning
confidence: 99%
“…Cai et al [36] derived the approximate solution of the first order Shear lag effects on pedestrian-induced vibration and TMD-based vibration control of footbridges vertical bending frequency for the simply supported curved thin-walled box girder considering the SLE. It has been reported that the SLE significantly affect the stiffness of the structures [35][36].…”
Section: Studies On the Shear Lag Effect (Sle) And Research Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study focused on a simply supported beam bridge on a high-speed railway, 23,24 analyzed the constraint effect of the rail in the subgrade section on both sides of the bridge, and derived the analytical expressions of the mapping relationship between the linear change of the beam and the deformation of the rail based on the principle of minimum potential energy. 2527 Through calculation, the mapping deformation curve of the rail in the CRTS I unit slab ballastless track–bridge system induced by pier subsidence and beam faulting was investigated in detail. Further, the present results were compared to the corresponding finite element numerical calculation results for analyzing the main influencing factors of rail deformation.…”
Section: Introductionmentioning
confidence: 99%